Resolva as equações de segundo grau, usando o método de Bhascara.

a) x²- 6x + 9 = 0

b) -x² + x + 12 = 0​


Resposta :

Resposta:

Explicação passo-a-passo:

a)

x  =  ( 6 +- [tex]\sqrt{36 - 4 . 9 . 1 }[/tex] )/2 . 1  =  ( 6 +- [tex]\sqrt{0}[/tex] )/2  =  6/2  = 3

                 

                            x = 3

b)

x = ( - 1 +- [tex]\sqrt{1 - 4 . - 1 . 12 }[/tex] )/2 .1   =  ( - 1 +- [tex]\sqrt{1 + 48}[/tex] )/ 2  =  (- 1   +-  7 )/2  

                     

                            x = - 3, 4